The New Map of Empire : How Britain Imagined America before Independence - Edelson, S. Max (Harvard University Press, 2017)
In 1763 British America stretched from Hudson Bay to the Keys, from the Atlantic to the Mississippi. Using maps that Britain created to control its new lands, Max Edelson pictures the contested geography of the British Atlantic world and offers new explanations of the causes and consequences of Britain's imperial ambitions before the Revolution.
Keywords: Cartography -- America -- History -- 18th century.; Surveying -- America -- History -- 18th century.; Cartographie -- Amérique -- Histoire -- 18e siècle.; HISTORY -- United States -- Colonial Period (1600-1775); Cartography; Surveying; America; 1700-1799; Electronic books.; History